2009
DOI: 10.1111/j.1471-6402.2009.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Child Sexual Abuse and Revictimization: The Mediating Role of Coping and Trauma Symptoms

Abstract: Child sexual abuse (CSA) has consistently been associated with the use of avoidant coping; these coping methods have been associated with increased trauma symptoms, which have, in turn, been linked to increased risk for adult sexual revictimization. Given these previous findings, the purpose of the current study was to test a model that conceptualized the relationships among these variables. Specifically, CSA severity was conceptualized as leading to the use of avoidant coping, which was proposed to lead to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
100
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 93 publications
11
100
0
Order By: Relevance
“…Spaccarelli (1994) found that among individuals who have experienced early sexual abuse, coping processes played a crucial mediating role in the development of symptomatology. In one population study (Fortier et al, 2009), childhood sexual abuse severity was associated with the use of avoidant coping, which, in turn, predicted greater levels of trauma symptomatology. In their notable review of the literature on child sexual abuse and coping, Walsh et al (2010) suggested that individuals who have more adaptive means of managing their sexual abuse-related negative emotions may experience less long-term distress than those who have greater difficulty processing such emotions.…”
Section: Abuse and Psycho-social Developmentmentioning
confidence: 98%
“…Spaccarelli (1994) found that among individuals who have experienced early sexual abuse, coping processes played a crucial mediating role in the development of symptomatology. In one population study (Fortier et al, 2009), childhood sexual abuse severity was associated with the use of avoidant coping, which, in turn, predicted greater levels of trauma symptomatology. In their notable review of the literature on child sexual abuse and coping, Walsh et al (2010) suggested that individuals who have more adaptive means of managing their sexual abuse-related negative emotions may experience less long-term distress than those who have greater difficulty processing such emotions.…”
Section: Abuse and Psycho-social Developmentmentioning
confidence: 98%
“…One explanation for this finding is that previously victimized women are at greater risk for trauma symptoms and/ or physiological arousal when faced with sexual coercion, which can lead them to feel overwhelmed and unable to respond (e.g., Fortier et al, 2009;Messman-Moore, Walsh, & DiLillo, 2010). If so, repeated practice in simulated high-risk situations may offer a form of exposure, reducing the potential effects of trauma symptoms or arousal on future behavioral responses.…”
mentioning
confidence: 91%
“…The link between adverse childhood experiences and subsequent trauma exposure is robust, and an extensive body of research indicates that women with a history of childhood sexual abuse (CSA) are at particularly high risk for later sexual revictimization (Arata, 2002; Fortier et al, 2009; Krahe, Scheinberger-Olwig, Waizenhofer, & Kolpin, 1999; Messman-Moore & Long, 2003; Widom, Czaja, & Dutton, 2008). Results from a meta-analysis by Roodman and Clum (2001) indicate that 15 to 79 percent of women reporting CSA also experience adult sexual assault (ASA), and a review by Classen, Palesh, and Aggarwal (2005) found that experiencing CSA doubles or even triples a woman’s risk for ASA.…”
mentioning
confidence: 99%